A Facile Surface Reconstruction Mechanism toward Better Electrochemical Performance of Li4Ti5O12 in Lithium‐Ion Battery. Issue 11 (10th July 2017) - Qian, Kun; Tang, Linkai; Wagemaker, Marnix; He, Yan‐Bing; Liu, Dongqing; Li, Hai; Shi, Ruiying; Li, Baohua; Kang, Feiyu
Abstract: Through a facile sodium sulfide (Na2 S)‐assisted hydrothermal treatment, clean and nondefective surfaces are constructed on micrometer‐sized Li4 Ti5 O12 particles. The remarkable improvement of surface quality shows a higher first cycle Coulombic efficiency (≈95%), a significantly enhanced cycling performance, and a better rate capability in electrochemical measurements. A combined study of Raman spectroscopy and inductive coupled plasma emission spectroscopy reveals that the evolution of Li4 Ti5 O12 surface in a water‐based hydrothermal environment is a hydrolysis–recrystallization process, which can introduce a new phase of anatase‐TiO2 . While, with a small amount of Na2 S (0.004 mol L −1 at least), the spinel‐Li4 Ti5 O12 phase is maintained without a second phase. During this process, the alkaline environment created by Na2 S and the surface adsorption of the sulfur‐containing group (HS − or S 2− ) can suppress the recrystallization of anatase‐TiO2 and renew the particle surfaces. This finding gives a better understanding of the surface–property relationship on Li4 Ti5 O12 and guidance on preparation and modification of electrode material other than coating or doping. Abstract : Clean and nondefective surfaces are constructed on Li4 Ti5 O12 particles through a facile sodium sulfide (Na2 S) assisted hydrothermal treatment. By improving the surface quality, a higher first cycle Coulombic efficiency (≈95%), a significantly enhanced cycling performance, and rate capability are realized, which highlight the newly discovered surface reconstruction mechanism and the surface–property relationship.